ANALYSIS OF INFORMATION ON THE SCIENCE OF TAFSIR AND HADITH IN THE WORK "FUTUH AL-BULDAN" (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article analyzes the information related to the sciences of tafsir and hadith in the work of Ahmad ibn Yahya al-Balazuri, Futuh al-Buldon. The main focus of this work is the spread of Islam across Asia and Africa during the early centuries, yet it also includes valuable information on subjects such as tafsir, hadith, fiqh, and Arabic literature. The author of the article examines Quranic verses and hadiths, illustrating the interconnectedness of Islamic sciences and presenting historical events based on religious sources. The article further discusses how later mufassirun and scholars have utilized Futuh al-Buldon in their works.